2011
DOI: 10.5688/ajpe758162
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Instruction in US Health Professions Education

Abstract: Objective. To describe patient safety instruction in health professional curricula, including medicine, nursing, pharmacy, and dentistry. Methods. A systematic review of the literature from 1966 through 2010 was conducted using 6 databases and based on 3 search criteria: safety management, patient safety, and curriculum. Results. One hundred fifty-four articles were identified and 23 met inclusion criteria. A variety of educational methods have been used in health profession curricula to promote patient safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 46 publications
4
58
0
6
Order By: Relevance
“…Se necesita evidenciar que esta metodología mejora el logro de las competencias desde la perspectiva de la seguridad del paciente antes del ejercicio de la profesión médica 16 .…”
Section: Discussionunclassified
“…Se necesita evidenciar que esta metodología mejora el logro de las competencias desde la perspectiva de la seguridad del paciente antes del ejercicio de la profesión médica 16 .…”
Section: Discussionunclassified
“…These environments should enhance learning form mistakes by analysing what happened to gain a full understanding of the encounter without triggering a judgmental behaviour [22]. In order to acquire a level of mastery on patient safety competencies, nursing education uses appropriate teaching methods to supply the fundamental components of patient safety [1,3,4,[8][9][10]27]. Patient safety is a part of daily practice, however, is not yet included in all nursing education curricula [3].…”
Section: Health Professional Education In Patient Safety Survey (H-pementioning
confidence: 99%
“…Patient safety is becoming majorly important in delivering healthcare and education, both on a national and international level [2,6]. Due to the publications 'To Err Is Human' and 'Crossing the Quality Chasm', produced by the Institute of Medicine (IOM), the healthcare system shows an increased focus on patient safety [4,7,8]. The IOM defined patient safety as freedom from accidental injury.…”
Section: Introductionmentioning
confidence: 99%
“…3 To date, limited work has examined the integration of patient safety curricula into health professions education. 4,5 The most comprehensive review noted that research on instructional methods necessary to guide curricular change in patient safety is needed. 5 In terms of patient safety instruction in pharmacy education, 2 studies provided information on current practices.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The most comprehensive review noted that research on instructional methods necessary to guide curricular change in patient safety is needed. 5 In terms of patient safety instruction in pharmacy education, 2 studies provided information on current practices. 6,7 West-Strum et al found that, across 107 different pharmacy schools, safety science subjects were integrated into the majority of schools, but certain gaps were identified (eg, risk communication, FDA Sentinel Event Initiative).…”
Section: Introductionmentioning
confidence: 99%